What influences whether parents recognise COVID-19 symptoms, request a test and self-isolate: A qualitative study. - Lisa Woodland; Fiona Mowbray; Louise E Smith; Rebecca K Webster; Richard Amlôt; G James Rubin (PLoS ONE)
Background Using test, trace and isolate systems can help reduce the spread of COVID-19. Parents have the additional responsibility of using these systems for themselves and acting on behalf of their children to help control COVID-19. We explored factors associated with the use of England's NHS Test and Trace service among parents of school-aged children. Methods One-to-one telephone interviews with parents (n = 18) of school-aged (4 to 18 years) children living in England between 30 November to 11 December 2020. Data were explored using thematic analysis. Results Three themes and eight sub-themes emerged. In terms of recognising symptoms of COVID-19, parents needed prompting before recalling the main symptoms described by the NHS. Parents suggested several factors relating to the nature of the symptom(s) and contextual information that might lead to or prevent them from seeking a test. Although parents supported symptomatic testing and described trusting official sources of information (e.g., Government and NHS websites). However, some concerns were raised regarding the accuracy of test results, safety at testing centres and logistics of testing but none of the concerns appeared to prevent engagement with testing. Parents perceived adherence to testing and self-isolation as pro-social behaviour, although family resources and circumstances impacted their ability to adhere fully. Conclusions Our study identified several barriers to parents using NHS Test and Trace as needed. Information about the eligibility of testing (main symptoms of COVID-19 and the age of eligibility) needs to be more precise and resources provided to enable families to adhere to self-isolation if the efficiency of test, trace and isolate systems is to be optimised.